2004
DOI: 10.1002/ps.907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the systemic activity of simeconazole in comparison with that of other DMI fungicides

Abstract: The systemic activity of simeconazole (RS-2-(4-fluorophenyl)-1-(1H-1,2,4-triazol-1-yl)-3-trimethylsilylpropan-2-ol) in plants was compared with those of eight other sterol demethylation inhibitor (DMI) fungicides. Simeconazole prevented the infection of Blumeria graminis (DC) Speer f sp hordei Marchal on barley leaves within a radius of several centimeters from the edge of local treatment on the leaves when the compound was separated from the leaves by glass coverslips. This reveals that simeconazole has promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…In our study, the customized triple‐nozzle system, with one nozzle above the canopy and one nozzle on each side, increased the capacity to apply more of the active ingredient into the center of the lower canopy layer compared with conventional spray. Active ingredients of most fungicide products are only minimally translocated within plants (Tsuda et al, 2004), thus the efficacy of pesticides for disease control is largely dependent on the deposition and retention of a sufficient concentration of the active ingredient on the crop canopy (Gossen et al, 2008). The application of fungicides with the triple‐nozzle systems, combined with the paired‐row spacing, was more efficient at directing fungicide droplets to the lower part of the crop canopy compared with a conventional horizontal boom sprayer.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the customized triple‐nozzle system, with one nozzle above the canopy and one nozzle on each side, increased the capacity to apply more of the active ingredient into the center of the lower canopy layer compared with conventional spray. Active ingredients of most fungicide products are only minimally translocated within plants (Tsuda et al, 2004), thus the efficacy of pesticides for disease control is largely dependent on the deposition and retention of a sufficient concentration of the active ingredient on the crop canopy (Gossen et al, 2008). The application of fungicides with the triple‐nozzle systems, combined with the paired‐row spacing, was more efficient at directing fungicide droplets to the lower part of the crop canopy compared with a conventional horizontal boom sprayer.…”
Section: Discussionmentioning
confidence: 99%
“…The active ingredients of the triazole group have curative effects, interfering with ergosterol biosynthesis in the fungal membrane and being absorbed by leaf tissues (Tsuda et al 2004). According to Koehle et al (2002), the fungicides of the strobilurin group interfere with spore germination and on the development of the germ tube and, like the triazols, move in a translaminar way.…”
Section: Short Cycle Cultivarsmentioning
confidence: 99%
“…The systemic properties of DMI and QoI fungicides are far more defined than those of flutolanil. Studies conducted by Tsuda et al (2004) documented the translaminar (movement from the upper leaf surface to the lower leaf surface) and transcuticular (movement through the cuticle) activity of several DMI fungicides, including tebuconazole. They found that fungicide efficacy against powdery mildew (Sphaerotheca cucurbitae (Jaczewski) Zhao) on cucumber (Cucumis sativus L.) seedlings resulted from permeation and dissipation of the fungicides within leaves.…”
Section: Evaluation Of Fungicidesmentioning
confidence: 99%